AN ANALYSIS OF TYPES OF ADVERBIAL CLAUSE IN MOVIE ALICE IN WONDERLAND - Febriany, Mariaty; Handayani, Nurma Dhona (Asosiasi dosen IDEBAHASA KEPRI, 2024)
This descriptive qualitative research aimed to investigate the types of adverbial clauses in the movie